Cognitive complaints are associated with smaller right medial temporal gray-matter volume in younger postmenopausal women. Issue 11 (November 2020) - Conley, Alexander C.; Albert, Kimberly M.; Boyd, Brian D.; Kim, Shin-Gyeom; Shokouhi, Sepideh; McDonald, Brenna C.; Saykin, Andrew J.; Dumas, Julie A.; Newhouse, Paul A.
Abstract: Objective: Menopause is associated with increasing cognitive complaints and older women are at increased risk of developing Alzheimer disease compared to men. However, there is difficulty in early markers of risk using objective performance measures. We investigated the impact of subjective cognitive complaints on the cortical structure in a sample of younger postmenopausal women. Methods: Data for this cross-sectional study were drawn from the baseline visit of a longer double-blind study examining estrogen-cholinergic interactions in normal postmenopausal women. Structural Magnetic Resonance Imaging was acquired on 44 women, aged 50-60 years and gray-matter volume was defined by voxel-based morphometry. Subjective measures of cognitive complaints and postmenopausal symptoms were obtained as well as tests of verbal episodic and working memory performance. Results: Increased levels of cognitive complaints were associated with lower gray-matter volume in the right medial temporal lobe ( r  = −0.445, P  < 0.002, R 2  = 0.2). Increased depressive symptoms and somatic complaints were also related to increased cognitive complaints and smaller medial temporal volumes but did not mediate the effect of cognitive complaints. In contrast, there was no association between performance on the memory tasks and subjective cognitive ratings, or medial temporal lobe volume. Conclusions: The findings of the present study indicate that the level of reported cognitive complaints in postmenopausal women may be associated with reduced gray-matter volume which may be associated with cortical changes that may increase risk of future cognitive decline. N/A: Video Summary: http://links.lww.com/MENO/A626 . Abstract : Supplemental Digital Content is available in the text